Palynological and physicochemical data characterisation of honeys produced in the Entre-Douro e Minho region of Portugal - Feás, Xesús (2010)
Honey legislation has been addressed to establish the minimum marketing level of the product and the need for consumer protection through correct denominations. Research oriented toward assessment of floral origin and physicochemical properties may increase the commercial value of these products. The characteristics of thirty-one honeys produced in the Entre-Douro e Minho region in Portugal were studied. Pollen features and some physicochemical parameters (moisture, ash, pH, free acidity, electrical conductivity, hydroxymethylfurfural contain, apparent sucrose, reducing sugars and diastase activity) were determined. The samples were found to meet international honey specifications. The present study found a linear regression between the ash content of honeys and their specific conductivity. Five samples are listed as Eucalyptus honey, one sample as Citrus honey, and twenty-five samples as multifloral honeys. Of the total, 87.1% exceeded the quality parameters and should be labelled as ‘virgin’ honey.